tmux Taster - McDonnell, Mark (Springer eBooks, 2014)
tmux Taster is your short, concise volume to learn about tmux, the terminal multiplexer that allows you to multiplex several virtual consoles. With tmux you can access multiple separate terminal sessions inside a single terminal window or remote terminal session, and do so much more. Through the seven to-the-point chapters, you'll learn the fundamentals of tmux, scripting and automation, pane and window management, pair programming, and workflow management. Increase your productivity by using a terminal multiplexer - start with tmux Taster today.